2016
DOI: 10.4267/2042/58718
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the permeability of polygonal faults from their intersection geometries with Linear Chimneys: a case study from the Lower Congo Basin

Abstract: Layer-bound arrays of polygonal compaction faults have long been considered as important migration routes for hydrocarbon fluids leaking to the surface across thick shale sequences. A classic example is the deep offshore of the Lower Congo Basin where numerous fluid-venting structures are present above a Pliocene polygonal fault system. In this paper we present a detailed seismic analysis of a newly recognised system of Quaternary-aged Linear Chimneys and their intersection geometries with pre-existing Pliocen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…2b). These intervals are deformed by polygonal faulting, which conforms to two distinct tiers, named here as Tier-1 and Tier-2 (Ho et al, 2012a(Ho et al, , 2016(Ho et al, , 2018Ho, 2013). The deepest Tier-1 ranges from 70-130 m thick and contains the Late Miocene units, whilst the shallower Tier-2 contains the Pliocene units and has a maximum thickness of ca.…”
Section: Miocene To Quaternary Stratigraphy and Elementsmentioning
confidence: 99%
“…2b). These intervals are deformed by polygonal faulting, which conforms to two distinct tiers, named here as Tier-1 and Tier-2 (Ho et al, 2012a(Ho et al, , 2016(Ho et al, , 2018Ho, 2013). The deepest Tier-1 ranges from 70-130 m thick and contains the Late Miocene units, whilst the shallower Tier-2 contains the Pliocene units and has a maximum thickness of ca.…”
Section: Miocene To Quaternary Stratigraphy and Elementsmentioning
confidence: 99%
“…In addition, mineralized fluids intensify diagenesis in the fracture planes, rendering this interval all the more impermeable (Laurent et al, 2012). The detailed analysis of the geometric relationships between highimpedance seismic anomalies and polygonal fault pairs reveals that they can act as a seal during early stages of burial (Ho et al, 2016). In the Congo Basin, the Pliocene-present interval contains widespread fluid escape features, at seabed and in the subsurface, indicating past and ongoing bypass of the regional seal which is intensely affected by a major polygonal fault system (Gay et al, 2004).…”
Section: Organic Matter Preservation and Shallow Fluid Migrationmentioning
confidence: 99%
“…The morphology of structures formed during fluid leakage records the style and intensity of fluid expulsion and is thus useful for deciphering the fluid migration history (Roberts et al, 2006;Blouet et al, 2017;Imbert et al, 2017;Imbert and Ho, 2012;Ho et al, 2012bHo et al, , 2018. As 3-D seismic reflection data have played an increasingly important role in visualisation and identification of fluid flow features (Heggland, 1997), by conducting seismic analyses for vertical successions of fluid leakage expressions around faults, such as gas chimneys feeding pockmarks and seep carbonates, it is possible to unravel the timing and pathways of migrating fluids and the sealing efficiency of faults (Ligtenberg, 2005;Plaza-Faverola et al, 2012;Ho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from the upper slope of the Lower Congo Basin have revealed the existence of a new type of chimney (Ho et al, 2016;Ho, 2013). Chimneys are usually circular in planform.…”
Section: Introductionmentioning
confidence: 99%